INDIVIDUAL WORK WITH THE VICTIM OF A CRIMINAL OFFENSE UNDER THE CONDITIONS OF THE STATE OF MARTIAL - Кривонос, Максим (SWorldJournal, 2023)
The article highlights the problems of individual work with the victim, in particular, the interrogation of the victim of a criminal offense in the conditions of the legal regime of martial law. The peculiarities and tactics of carrying out the specified